Distribution of human fecal marker genes and their association with pathogenic viruses in untreated wastewater determined using quantitative PCR. (1st November 2022) - Ahmed, Warish; Bivins, Aaron; Payyappat, Sudhi; Cassidy, Michele; Harrison, Nathan; Besley, Colin
Highlights: Human fecal marker genes and GC of pathogenic viruses were measured in wastewater. GC of pathogenic viruses were 3-5 orders of magnitude lower than human fecal marker genes. The concentrations of pathogenic viral GC were highly variable over the course of the study. HF183, CrAssphage and PMMoV correlated well with GC of pathogenic viruses. Abstract: Quantitative microbial risk assessment (QMRA) of human health risks using human fecal marker genes (HFMGs) is an useful water quality management tool. To inform accurate QMRA analysis, generation of probability distribution functions for HFMGs, and reference pathogenic viruses can be improved by input of correlation and ratios based upon measurement of HFMGs and gene copies (GC) of pathogenic viruses in untreated wastewater. The concentrations of four HFMGs ( Bacteroides HF183, Lachnospiraceae Lachno3, CrAssphage and pepper mild mottle virus (PMMoV)), and GC of three reference pathogenic viruses human adenovirus 40/41 (HAdV 40/41), human norovirus GI + GII HNoV GI + GII and enterovirus (EV) were measured in untreated wastewater samples collected over a period of 12 months from two wastewater treatment plants in Sydney, Australia using quantitative polymerase chain reaction (qPCR) and reverse transcription qPCR (RT-qPCR). Over the course of the study, the GC of potential pathogenic viruses were 3–5 orders of magnitude lower than HFMGs in untreated wastewater. The GC of pathogenic viruses were highly variable over the course of the study, which contrasted with the concentrations of HFMGs that were quite stable with little variation observed within and between WWTPs. Among the HFMGs, HF183, CrAssphage and PMMoV correlated well with pathogenic virus GC, whereas weak or negative correlations were observed between Lachno3 and pathogenic virus GC. While the two assessed WWTPs had dissimilar population service sizes, the ratios between log10 transformed pathogenic virus GC and HFMGs demonstrated similar central tendency and variability for the same combinations between WWTP A and WWTP B with no difference between the WWTPs. This suggests the widespread presence of these HFMGs in both populations serviced by these two WWTPs. The observed correlation and ratios of HFMGs and GC of reference pathogenic viruses can contribute to improved QMRA of human health risks in environmental waters subject to fresh sewer overflows. Graphical abstract: Image, graphical abstract